Avaliação da toxicidade e atividade anti-helmíntica de Momordica charantia - Fonseca, Zuliete Aliona Araujo de Souza (Universidade Federal Rural do Semi-Árido, 2016)
Gastrointestinal nematodes of small ruminants cause severe pathology and are a major cause of economic losses in sheep and goat farming, particularly in tropical and subtropical areas worldwide. Therefore, the development of sustainable, environmentally acceptable methods of nematode control has become a necessity. To evaluate the anthelmintic action of hydroalcoholic extract of Momordica charantia (EHMC) in the control of gastrointestinal nematodes of sheep, the egg hatch test (EHT), larval development test (LDT), and toxicity test using mices Balb/c and reduced eggs count in the feces (FECRT), were conducted. To evaluate the anthelmintic efficacy in vitro, TEO and TDL tests were conducted using EHMC at concentrations of 0.05; 0.1; 0.3; 0.7; 1.5 mg ml-1 on eggs and larvae of Haemonchus contortus. For the toxicity tests, Balb/c mice were randomly divided in groups (n = 12), based on the following treatments: 4.000 (G1), 6.000 (G2), 8.000 (G3), 10.000 mg.kg-1 (G4) and control group (G5), administered by gavage and observed for 14 days. To evaluate the anthelmintic action in vivo, 50 sheep naturally infected were randomly divided into five groups (n=10 per group) where: G1 was the control group, G2 was treated with 350 mg kg-1 EHMC, G3 with 7.5 mg kg-1 of Levamisole, G4 with 0.2 mg.kg-1 of Ivermectina and G5 with 10 mg.kg-1 of Albendazol. The efficacy on the control of gastrointestinal nematodes was valued 7, 14 and 21 days after treatment for the calculation of the fecal egg count reduction test (FECRT). In the in vitro tests, the EHMC turned out to be very effective by reducing 98.81% of the hatching eggs and the development 99.61% of H. contortus larvae in the dose of 1.5 mg.ml-1. In the acute toxicity test, the EHMC produced no signs of toxicity or death at a concentration of 4.000 mg kg-1, showing that doses below that value are considered safe for use in sheep naturally infected. In the FECRT, the reduction in OPG in sheep was 57% and 56% for EHMC, 93% and 74% for levamisole on days 7 and 14 after treatment, respectively. On day 14 after treatment, there was no significant difference between EHMC and levamisole (p<0.05), there was a reduction of 54% and 69% of excretion of eggs of Haemonchus and Trichostrongylus respectively in the group treated with EHMC in the same period. We conclude that the hydroalcoholic extract of M. charantia showed significant anthelmintic effect in vitro and in vivo, providing an alternative for the control of gastrointestinal nematodes in sheep
Evaluation of toxicity and anthelmintic activity of Momordica charantia
Keywords: Fitoterápico; Helmintose; Ovinos; Haemonchus contortus; Herbal medicine; Helminths; Sheep; Haemonchus contortus; CIENCIAS AGRARIAS::MEDICINA VETERINARIA